ФІНАНСОВИЙ МЕХАНІЗМ СИСТЕМИ СОЦІАЛЬНОГО ЗАХИСТУ НАСЕЛЕННЯ УКРАЇНИ - Жук, Олег Богданович (Науковий журнал «Світ фінансів», 2017)
Жук О. Б. Фінансовий механізм системи соціального захисту населення України. Проаналізовано та узагальнено погляди науковців щодо визначення сутності та структури фінансового механізму системи соціального захисту населення. Запропоновано авторське визначення понять “соціальний захист”, “фінансовий механізм системи соціального захисту населення” та “фінансове забезпечення соціального захисту населення”. Подано авторську структуру вітчизняного фінансового механізму системи соціального захисту населення, розроблено рекомендації щодо його вдосконалення в умовах реформування національної економіки. Жук О. Б.Финансовый механизм системы социальной защиты населения Украины. Проанализированы и обобщены взгляды учёных относительно определения предмета и структуры финансового механизма системы социальной защиты населения. Предложено авторское определение понятий “социальная защита”, “финансовый механизм системы социальной защиты населения” и “финансовое обеспечение социальной защиты населения”. Представлена авторская структура отечественного финансового механизма системы социальной защиты населения, разработаны рекомендации по его совершенствованию в условиях реформирования национальной экономики. Zhuk O. Financial mechanism of people’s social protection system in Ukraine. Introduction. Implementation of effective and acting policy of people’s social protection demands the creation of an appropriate financial mechanism of its realization that could be able to provide a significant welfare increasing of every citizen of Ukraine.Purpose. The purpose of the article is to research theoretical, methodological, organizational and practical aspects of functioning the financial mechanism of people’s social protection system in Ukraine and to develop recommendations for its improvement in terms of transformation of the national economy, considering the current socio-economic and military-political situation in the country.Results. The views of some authors to determine the nature and structure of the financial mechanism of people’s social protection system in Ukraine are analyzed and summarized. The author suggests his own definition of the concepts of “social protection”, “financial mechanism of people’s social protection system” and “financial support of people’s social protection”. The structure of the domestic financial mechanism of people’s social protection system that includes groups of four main elements (financial and organizational forms, financial methods, financial instruments and financial levers) are presented by the author.Conclusion. Improving the financial mechanism of PSPS in Ukraine there should be achieving an effective and mutual cooperation and interaction of financial mechanisms of structural components of the social protection system: social insurance, social support, social standards and guarantees of the state to its population.